Nutrition Education and Vitamin D Supplementation Improving Nutrition Intake, Body Composition, and Vitamin D Status of Soccer Athlete - Weni Kurdanti; Agus Wijanarka; Mirza Hapsari Sakti Titis Penggalih (Amerta Nutrition)
Background: The success of soccer athletes is influenced by physical, mental, and genetic factors, with nutritional status significantly affects youth soccer performance in Indonesia by 69.8%. Body composition and somatotype are critical components of nutritional status. Biochemical indicators such as creatine kinase (CK) and vitamin D levels provide insights into the impact of training and diet on athletes.